The Impact of COVID-19 Uncertainty on Warsaw Stock Exchange Quotations - Wojciech KACZMARCZYK (Communications of International Proceedings, 2021)
The pandemic of COVID-19 had a significant impact on the stock exchanges, including the Warsaw Stock Exchange. This impact was assessed by analysing indexes and sub-indexes of WSE for period from 1st January 2019 to 30th September 2021. Daily logarithmic average rates of return, transaction volumes, standard deviations and daily price fluctuations were measured. The calculations were made for quarterly periods, as well as additionally for March 2020. In the case of WSE, there were large drops and an increase in uncertainty in Q1 2020, later the valuations started were increasing and the uncertainty gradually decreased, reaching 2019 levels, regardless of the pandemic situation. Additionally, the least negative impact was recorded in the case of innovative sectors.
Keywords: COVID-19; Warsaw Stock Exchange